(untitled) (Research, Society and Development, 2022)
Oriented strand board (OSB) is an important engineered wood product, manufactured by gluing strand particles in cross layers, being widely applied in construction, packaging, decking, flooring, wall cladding and even for load-bearing purposes. For the production of these panels, we can use biomass from agriculture, as residues from the coffee activity. The objective of this research was to evaluate the chemical composition of coffee and pine wood, as well as the physical and mechanical properties of the panels produced with the replacement of pine by waste. The OSB panels produced used the replacement of pine for coffee wood at 0 (T1), 25 (T2), 50 (T3), 75 (T4) and 100% (T5). The results show that there were significant improvements in the physical-mechanical properties and that the treatments met the minimum required by standard, with the exception of T2. Therefore, the potential of using coffee wood residue for the production of OSB panels is evidenced, since this bioproduct will avoid the incorrect destination of the residue and several other environmental problems.